HUBUNGAN PENGETAHUAN DENGAN SIKAP IBU HAMIL TENTANG PEMANFAATAN BUKU KIA - TJUT ALINI (JURNAL ILMIAH MAKSITEK, 2021)
Knowledge is the result of knowing, and this occurs after people have sensed a certain object. (Notoatmodjo, 2021).Attitudes are evaluative statements towards objects, people or events. It reflects one's feelings towards something.(Nurmala, et al. 2018). The sample in this study used a total sample, namely the sampling was carried out as a whole fromthe population, with a total of 30 respondents. Respondents who have poor knowledge of respondents are 18 people(60.0%) and those who have good knowledge are 12 respondents (40.0%). Respondents who have a negative attitude are19 people (63.3%) and a positive attitude is 11 people (36.7%). Respondents who have poor knowledge and negativeattitudes are 16 people (53.3%). Respondents who have poor knowledge and positive attitude are 2 people (6.7%).Respondents who have good knowledge and negative attitudes are 3 people (10.0%). Respondents who have goodknowledge and positive attitude are 9 people (30%). The results of statistical tests show that there is a relationship betweenknowledge and attitudes of respondents about the use of MCH books, with a p-value of 0.002.